Thermolysis troubles during an endurance training session on rowing ergometer in high-level oarsmen - Maciejewski, H.; Messonier, L.; Moyen, B.; Lacour, J. R.; Bourdin, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
As part of their regular training programme or when meteorological conditions do not allow training on boat, oarsmen employ extensively rowing ergometer. However, the ergometer is mainly used in enclosed rooms where ambient temperature and hygrometry are high and where the convection in relation to the boat speed and wind are lacking. In such conditions, the oarsmen might be exposed to thermolysis troubles during training. This may accelerate heat storage and reduce performance (Saltin et al. 1966). If this hypothesis is correct, the use of ventilators would improve heat loss and delay appearance of exhaustion. The main objective of the present study was to test this hypothesis. Methods Six high-level oarsmen performed on a rowing ergometer 1) an incremental exercise to determine the power output corresponding to 2.5 mmol·l-1 of blood lactate concentration (P2.5) and 2) two 30 min constant workload exercises separated by a 10-min rest period. Each 30 min exercise period was performed in control (CC) and ventilated condition (VC). In the latter, two ventilators were placed in front of the rower (horizontal air flow) and a third one was placed below the rower (vertical air flow). The convection output was 1.07 m3·s-1. Heart rate (HR), oxygen uptake (VO2), blood lactate concentration ([La]b), rate of perceived exertion (RPE) and rectal temperature (Tre) were measured at the 3rd, 10th, 20th and 30th minute of each session in CC and VC. The Wilcoxon signed rank test was used for comparison between CC and VC and to appreciate the drifts of each parameter during the last twenty minutes of each exercise period. Significance was set at P<0.05. Results HR, VO2, [La]b and RPE displayed increases during exercise in both conditions. These increasesobserved in CC have been significantly reduced in VC, excepted for the [La]bprofile which stayed similar in CC and VC (Figure, Table).Tre and RPE reached at the end of the exercise was 38.6±0.5°C and 15.2±2.2 in CC and 38.2±0.5°C and 14.2±2.5 in VC. Discussion/Conclusion Tre reached by the oarsmen at the end of the exercise in CC was close to the critical temperature (39°C, Latzka et al. 1988). These high Tre associated with HR and VO2 drifts in CC seem to indicate that the thermoregulation processes are insufficient to eliminate the metabolic heat production. At the exception of [La]b, all the drifts observed in CC were significantly reduced in VC indicating that the thermolysis troubles linked to the lack of convection in relation to the boat speed and wind may be limited by artificially increased convection. However, the fact that [La]b presented the same profile in both conditions would suggest that [La]b profiles are to some extent independent of heat production. The lower RPE reached at the end of the exercise in VC seem also to show that the training is perceived as less exhaustive in VC. In conclusion, this study shows that the use of ventilators may limit thermolysis troubles met by high-level oarsmen during training on rowing ergometer.